2014
DOI: 10.1038/cr.2014.97
|View full text |Cite
|
Sign up to set email alerts
|

A Smad3 and TTF-1/NKX2-1 complex regulates Smad4-independent gene expression

Abstract: Thyroid transcription factor-1 (TTF-1, also known as NKX2-1) is a tissue-specific transcription factor in lung epithelial cells. Although TTF-1 inhibits the epithelial-to-mesenchymal transition induced by transforming growth factor-β (TGF-β) in lung adenocarcinoma cells, the mechanism through which TTF-1 inhibits the functions of TGF-β is unknown. Here we show that TTF-1 disrupts the nuclear Smad3-Smad4 complex without affecting the nuclear localization of phospho-Smad3. Genome-wide analysis by chromatin immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 41 publications
3
53
1
Order By: Relevance
“…RNA‐seq was performed as described previously (Isogaya et al ., 2014; Mizutani et al ., 2016). cDNA libraries were prepared using the RNeasy Mini Kit with the On‐Column DNase Digestion Set (QIAGEN, Venlo, The Netherlands), Dynabeads mRNA DIRECT Purification Kit, and the Ion Total RNA‐Seq Kit v2 (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…RNA‐seq was performed as described previously (Isogaya et al ., 2014; Mizutani et al ., 2016). cDNA libraries were prepared using the RNeasy Mini Kit with the On‐Column DNase Digestion Set (QIAGEN, Venlo, The Netherlands), Dynabeads mRNA DIRECT Purification Kit, and the Ion Total RNA‐Seq Kit v2 (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Further investigation revealed that NKX2-1 disrupts the Smad3-Smad4 complex in the nucleus and dramatically alters both the binding strength and distribution of Smad3 throughout the genome (Fig. 3A) [126]. In addition, NKX2-1 forms a complex with Smad3, but without Smad4, and the Smad3-NKX2-1 complex regulates the expression of target genes related to other processes of cancer, such as LMO3 [126].…”
Section: Tgf-β-induced Target Gene Expression and Emt In Lung Adenocamentioning
confidence: 99%
“…Since prior studies had shown that a large proportion of Smad-binding sites are found outside of promoter-proximal regions at putative enhancer elements (Kennedy et al 2011;Morikawa et al 2011;Schlenner et al 2012;Gaunt et al 2013), we considered whether Smad proteins occupy distal SBEs at the DOCK4 locus. To this end, we analyzed available Smad3 ChIP-seq (chromatin immunoprecipitation [ChIP] combined with deep sequencing) data (GSE51509) obtained from TGF-b-stimulated A549 cells (Isogaya et al 2014) and found two significant Smad3 peaks in the first intron of DOCK4 at +45 kb and +125 kb (Fig. 1I).…”
Section: Tgf-b Potently Induces Expression Of Dock4 Via the Smad Pathwaymentioning
confidence: 99%